Dependence of Zakat assistance among asnaf students in Universiti Teknologi Mara Terengganu Branch, Malaysia - Zakaria, Zainuddin; Jalil, Mohammad Syukri; Mohd Daud, Mohd Ariff; Sulaiman, Noor Hasyimah (Indonesian Journal of Islamic Economics Research, 2024)
This study wants to examine whether Zakat funds are used as well as possible by mustahik zakat The sample of data consists of asnaf students at the UiTM Terengganu Branch, including Dungun Campus, Bukit Besi Campus, and Kuala Terengganu Campus. The method of data collection is using a questionnaire that was created in accordance with the study sample, which is UiTM asnaf students. A sample of 164 students was taken for the three campuses at the UiTM Terengganu Branch. Data analysis using descriptive statistical analysis, i.e., Structure Equation Modelling (SEM), with data to be generated using the Smart PLS version 4.0.9.2. The results of the study found that the level of dependence on zakat aid among students is high, with four variables showing a significant effect, namely the knowledge factor, perception factor, exposure factor, and attitude factor. While the understanding factor is not significant for DZA.